From E-Learning to M-Learning - the use of Mixed Reality Games as a new Educational Paradigm - Fotouhi-Ghazvini, F.; Earnshaw, Rae; Moeini, Ali; Robison, David; Excell, Peter (International Journal of Interactive Mobile Technologies (iJIM), 2011)
This paper analyses different definitions of mobile learning which have been proposed by various researchers. The most distinctive features of mobile learning are extracted to propose a new definition for Mobile Educational Mixed Reality Games (MEMRG). A questionnaire and a quantifying scale are designed to assist the game developers in designing MEMRG. A new psycho-pedagogical approach to teaching is proposed for MEMRG. This methodology is based on the theme of â??conversationâ?? between different actors of the learning community with the objective of building the architectural framework for MEMRG.